2021
DOI: 10.1108/apjml-06-2020-0408
|View full text |Cite
|
Sign up to set email alerts
|

Architectural design and consumer experience: an investigation of shopping malls throughout the design process

Abstract: PurposeThe purpose of this paper is to identify the design elements of environmental features that affect consumer experience in shopping malls and develop a comprehensive understanding of the relationship between architectural design and consumer experience.Design/methodology/approachThrough the systematic literature review, 13 design elements were obtained and then verified through interviews of 30 professional designers. The obtained elements were made into a questionnaire to collect data across China from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…Third, our results, indicate that the experiential value is critical across different countries and can be applied to a wider scope, such as experiential values in AR (augmented reality) based display at shops (Xu et al, 2019) and omni-channel settings (Chen et al, 2020), shopping experience design and brand experience management (Mostafa and Kasamani, 2020;Yuan et al, 2021) or customer journey map (CJM) design (Kuehnl et al, 2019). These designs and experience management will lead to customer values which connect and lead to our framework as the consequences (i.e.…”
Section: Discussionmentioning
confidence: 75%
“…Third, our results, indicate that the experiential value is critical across different countries and can be applied to a wider scope, such as experiential values in AR (augmented reality) based display at shops (Xu et al, 2019) and omni-channel settings (Chen et al, 2020), shopping experience design and brand experience management (Mostafa and Kasamani, 2020;Yuan et al, 2021) or customer journey map (CJM) design (Kuehnl et al, 2019). These designs and experience management will lead to customer values which connect and lead to our framework as the consequences (i.e.…”
Section: Discussionmentioning
confidence: 75%
“…In the third sphere in the literature, the impact of PED based on different perceptions and other promotional methods, researchers (Jang et al, 2018;Blazquez et al, 2019;Yildirim et al, QMR 25,2 2020) have suggested that each medium is different and therefore has its own reputation, which results in different levels of perception regarding PED for each one. Yuan et al (2021) examined the effects of music, light, thermal settings, aroma and security on consumers' psychology. These results were also validated by Imschloss and Kuehnl (2017) and Yuan et al (2021), who established a difference between the PED and sensorium, behaviour and happiness and concluded that excitement and pleasure level was higher for the in-store consumers than for the virtual shoppers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yuan et al (2021) examined the effects of music, light, thermal settings, aroma and security on consumers' psychology. These results were also validated by Imschloss and Kuehnl (2017) and Yuan et al (2021), who established a difference between the PED and sensorium, behaviour and happiness and concluded that excitement and pleasure level was higher for the in-store consumers than for the virtual shoppers. Similar, findings were also found by Chatterjee (2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations